2006
DOI: 10.1096/fj.06-6113com
|View full text |Cite
|
Sign up to set email alerts
|

Human ACE and bradykinin B 2 receptors form a complex at the plasma membrane

Abstract: To investigate how angiotensin-I converting enzyme (ACE) inhibitors enhance the actions of bradykinin (BK) on B 2 receptors independent of blocking BK inactivation, we expressed human somatic ACE and B 2 receptors in CHO cells. Bradykinin and its ACE-resistant analogue were the receptor agonists. B 2 fused with green fluorescent protein (GFP) and ACE were coprecipitated with antisera to GFP or ACE shown in Western blots. Immunohistochemistry of fixed cells localized ACE by red color and B 2 -GFP by green. Yell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 49 publications
(111 reference statements)
2
28
0
5
Order By: Relevance
“…However, there is emerging evidence that analogous protein assemblies may occur on the cell surface, possibly in lipid microdomains (41)(42)(43). Although interactions between peptide receptors and related peptidases have not been extensively studied, recent evidence indicates that ACE and B2 kinin receptor do interact on the cell surface (44,45). Because ACE readily inactivates bradykinin, it was previously thought that ACE inhibitors enhance B2R signaling solely by blocking degradation of the B2 agonist (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is emerging evidence that analogous protein assemblies may occur on the cell surface, possibly in lipid microdomains (41)(42)(43). Although interactions between peptide receptors and related peptidases have not been extensively studied, recent evidence indicates that ACE and B2 kinin receptor do interact on the cell surface (44,45). Because ACE readily inactivates bradykinin, it was previously thought that ACE inhibitors enhance B2R signaling solely by blocking degradation of the B2 agonist (46).…”
Section: Discussionmentioning
confidence: 99%
“…with ACE-resistant B2 agonists) (47). Subsequent studies showed that ACE and B2Rs form heterodimers on the cell membrane and are co-localized in the same membrane microdomain (44,45), indicating that conformational changes in ACE upon inhibitor binding are transmitted to the B2R, which results in allosteric modification of its signaling properties.…”
Section: Discussionmentioning
confidence: 99%
“…Формирование комплексов АПФ-Б 2 Р на клеточной мембране в культуре СНО-клеток позднее было подтверждено методом иммуногистохимии с использованием флуоресцентной микроскопии [83]. В качестве стимуляторов Б 2 Р были взяты Бк и его аналог, устойчивый к действию АПФ.…”
Section: активация рецепторов кининов ингибиторами апфunclassified
“…L'implication de la BK dans l'effet des IEC reste une source de débats contradictoires, souvent explicables par les méthodologies de mesure de la BK, celles des prélèvements sanguins, ainsi que par les conditions physiopathologiques et expérimentales (âge, régimes alimentaires, imprégnation hormonale, hypertension) qui induisent un niveau d'activité variable du SKK. Un nouveau mécanisme additionnel d'action des IEC reposerait sur la formation d'un complexe membranaire entre l'enzyme de conversion de l'angiotensine (ECA) et le RB2 (complexe ECA/RB2) qui augmenterait la sensibilité du RB2 pour la bradykinine [3]. Par ailleurs, le traitement par les IEC entraîne l'accumulation d'angiotensine I dégradée en angiotensine 1-7 par plusieurs enzymes.…”
Section: Rôle De La Bradykinine Dans Le Mécanisme D'action Des Iecunclassified